Advances in RNA cytosine-5 methylation: detection, regulatory mechanisms, biological functions and links to cancer - Chen Xue; Yalei Zhao; Lanjuan Li (BMC, 2020)
Abstract As an important posttranscriptional modification of RNA, 5-methylcytosine (m5C) has attracted increasing interest recently, with accumulating evidence suggesting the involvement of RNA m5C modification in multiple cellular processes as well as tumorigenesis. Cooperatively, advances in m5C detection techniques have enabled transcriptome mapping of RNA methylation at single-nucleotide resolution, thus stimulating m5C-based investigations. In this review, we summarize currently available approaches for detecting m5C distribution in RNA as well as the advantages and disadvantages of these techniques. Moreover, we elucidate the regulatory mechanisms of RNA m5C modification by introducing the molecular structure, catalytic substrates, cellular distributions and biological functions of RNA m5C regulators. The functional consequences of m5C modification on mRNAs, tRNAs, rRNAs and other RNA species, including viral RNAs and vault RNAs, are also discussed. Finally, we review the role of RNA m5C modification in cancer pathogenesis and progression, in hopes of providing new insights into cancer treatment.